The Complex Evaluation of the Impact of COVID-19 Pandemic at Universities: A Soft Computing Approach - František Zapletal; Miroslav Hudec; Miloš Švaňa; Lucie Chytilová; Karel Hlaváček; Aleš Lokaj; Anna Urbanek; Jozef Glova; João Paulo Samartinho; Cristina Maria Costa Rodriguez; Stefán Guðnason (Journal on Efficiency and Responsibility in Education and Science, 2023)
The COVID-19 pandemic impacted the educational process since the teaching process has been forced to go online in many countries. This enforced change revealed the weaknesses and strengths of the national educational systems and particular institutions. This article aims to analyse the impact of COVID-19 at selected European universities and assess the satisfaction of students, teachers, IT staff and management. This study is unique for its systematicity and complexity – it aggregates the opinions of all interested groups of stakeholders, distinguishes several time periods (before, during and after the pandemic), and allows the respondents to express hesitance in their evaluation. The evaluation model uses fuzzy sets to capture the uncertainty and to aggregate the opinions of different stakeholder groups. The empirical results show that most of the satisfaction development is the same or similar for all institutions examined. Then, the pandemic strongly influenced the satisfaction of all stakeholder groups at the universities examined. This impact was mostly negative, however, several lessons learnt have been revealed. Therefore, it was shown that it is highly beneficial to include these aspects to obtain a reliable picture of overall satisfaction.